In Vivo Expression of and Cell-Mediated Immune Responses to the Plasmid-Encoded Virulence-Associated Proteins of Rhodococcus equi in Foals - Jacks, Stephanie (American Society for Microbiology, 2007)
Rhodococcus equi is a facultative intracellular pathogen that causes pneumonia in foals but does not induce disease in adult horses. Virulence of R. equi depends on the presence of a large plasmid, which encodes a family of seven virulence-associated proteins (VapA and VapC to VapH). Eradication of R. equi from the lungs depends on gamma interferon (IFN-γ) production by T lymphocytes. The objectives of the present study were to determine the relative in vivo expression of the vap genes of R. equi in the lungs of infected foals, to determine the recall response of bronchial lymph node (BLN) lymphocytes from foals and adult horses to each of the Vap proteins, and to compare the cytokine profiles of proliferating lymphocytes between foals and adult horses. vapA, vapD, and vapG were preferentially expressed in the lungs of infected foals, and expression of these genes in the lungs was significantly (P < 0.05) higher than that achieved during in vitro growth. VapA and VapC induced the strongest lymphoproliferative responses for foals and adult horses. There was no significant difference in recall lymphoproliferative responses or IFN-γ mRNA expression by bronchial lymph node lymphocytes between foals and adults. In contrast, interleukin 4 (IL-4) expression was significantly higher for adults than for foals for each of the Vap proteins. The ratio of IFN-γ to IL-4 was significantly higher for foals than for adult horses for most Vap proteins. Therefore, foals are immunocompetent and are capable of mounting lymphoproliferative responses of the same magnitude and cytokine phenotype as those of adult horses.